Unexpected art: serendipitous installations, site specific works, and surprising interventions - Moussa Spring, Jenny
Graffiti made from cake icing, man made clouds floating indoors, a luminous moon resting on water. Collected here are dozens of jaw-dropping artworks site specific installations, extraordinary sculptures, and groundbreaking interventions in public space that reveal the exciting things that happen when contemporary artists play with the idea of place. Unexpected Art showcases the wonderfully experimental work of more than 50 innovative artists from around the world in galleries of their most astonishing artworks. An unusual package with three different colored page edges complements the art inside and makes this tour of the world's most mind-blowing artwork a beautiful and thoughtprovoking gift for anyone interested in the next cool thing